2014
DOI: 10.3348/kjr.2014.15.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Small Bowel Obstruction Caused by Peritoneal Immunoglobulin G4-Related Disease Mimicking Carcinomatosis: Case Report

Abstract: We hereby report a case of diffuse pelvic peritoneal involvement by immunoglobulin G4-related disease (IgG4-RD). Numerous pelvic masses and nodules showing delayed enhancement on enhanced abdominal CT were found to congregate in the pelvic organs of a 57-year-old female presenting with intestinal subocclusion. The differentiation between peritoneal IgG4-RD and pelvic peritoneal carcinomatosis was only made by histopathology and immunohistochemistry performed after surgical resection. Autoimmune pancreatitis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…In previous case reports, most omental involvement IgG4-RD is associated with small bowel or colons. 2,17 Because of its rarity and no specific imaging consensus, 18 even experienced surgeons could misdiagnose IgG4related diseases as renal pelvis tumor, retroperitoneal tumor or lymphoma. In this case, urothelial carcinoma was highly suspicious initially based on urine cytology and computed tomography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous case reports, most omental involvement IgG4-RD is associated with small bowel or colons. 2,17 Because of its rarity and no specific imaging consensus, 18 even experienced surgeons could misdiagnose IgG4related diseases as renal pelvis tumor, retroperitoneal tumor or lymphoma. In this case, urothelial carcinoma was highly suspicious initially based on urine cytology and computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…In some even rarer situations, it presents as peritoneal carcinomatosis. 2 Definite diagnosis is based on immunohistochemistry. The first line of treatment for IgG4-RD is glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of biliary tree is the second most frequent, followed by the major salivary glands, kidney, gall bladder, and retroperitoneum ( 2 ). Although IgG4-related disease involving the gastrointestinal tract is very rare, there are reports of IgG4-related disease involving the esophagus, stomach, duodenum, ileum, and colon ( 3 4 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of IgG4 with sclerosing diseases was firstly described in 2001 by Hamano et al ( 4 ), who reported an elevated serum IgG4 level in patients with autoimmune pancreatitis. Since 2003, extra-pancreatic manifestations have been reported and the disease has been recognized as a systemic disease ( 5 6 7 8 9 10 11 ). Elevated serum IgG and IgG4 levels and the presence of autoantibodies (e.g., rheumatoid factor, antinuclear antibodies) may help in the diagnosis of IgG4-SD.…”
Section: Discussionmentioning
confidence: 99%